Pengaruh Massage Effleurage Dengan Minyak Atsiri Biji Pala (Myristica Fragrans) untuk Mengurangi Nyeri Betis pada Pekerja Wanita Pabrik Sarden di Jembrana - Ayu Gina Musttika; Ni Ketut Dewi Irwanti; Dwi Prima Hanis Kusumaningtiyas (Jurnal Medicare, 2026)
Introduction: Musculoskeletal pain in the lower extremities, especially calf pain, is commonly experienced by industrial workers and may reduce productivity. Effleurage massage with nutmeg essential oil has the potential to serve as a non-pharmacological therapy to help reduce pain. Objective: This study aimed to determine the effect og effleurage massage with nutmeg essential oil on the reduction of calf pain among female workers in a sardine factory in Jembrana. Methods: this study used a pre-experimental design with a one-group pretest-posttest approach. The sampel consisted of 38 female workers selected by purposive sampling. Pain intensity was measured using the numeric rating scale (NRS) before and after the intervention. The intervention was applied for three consecutive days using 5 mL of nutmeg seed essential oil, witch each sesion lasting 15 minutes. Data were analyzed using the Wilcoxon Signed Rank Test at a significance level of 0,05. Results:The results showed a decrease in calf pain scores after the effleurage massage intervention with nutmeg essential oil. The was a significant difference in pain intensity before and after the intervention. Conclusion: eflleurage massage with nutmeg essential oil was effective in reducing calf pain among female workers in the sardine factory in Jembrana.